Study of the Temperature Influence on an Electret Microphone in the Monitoring of Fused Deposition Modeling † - Lopes, Thiago Glissoi [UNESP]; Aguiar, Paulo Roberto [UNESP]; Junior, Cristiano Soares [UNESP]; de Oliveira Junior, Reinaldo Götz [UNESP]; Monson, Paulo Monteiro Carvalho [UNESP]; David, Gabriel Augusto [UNESP] (MDPI, 2023)
The evaluation of the response of sensors fixed to the print bed in the fused filament fabrication (FFF) process has been the subject of recent studies due to the increasing use of the FFF process. Many of these studies focus on topics related to monitoring the FFF process through the signals collected by sensors. Recently, some works employing piezoelectric diaphragm and electret microphones can be found in the monitoring of the FFF process, but the influence of the transducer response due to the variation of temperature has not been addressed. Thus, this work presents a study of the response of a low-cost electret microphone attached to the print bed under different temperature values. A 3D printer with polylactic acid (PLA) filament was used in the tests, which consisted of applying the pencil lead break method (PLB on the heated print bed at temperature values ranging from 25 °C to 65 °C. The acoustic waves generated by the tests were captured by the electret microphone attached near the breakage point, and the signals were sampled using an oscilloscope at a frequency of 2 MHz. The signals were processed in the time and frequency domains, followed by comparative analyses between the signals obtained for different temperature values. The results showed that it was not possible to determine a single temperature value at which the response of the electret microphone starts to undergo significant changes, but rather there is inconsistent change in the transducer’s response across all frequency bands, indicating that the influence of temperature takes place in a complex way as frequency varies. This complexity is further evidenced by the non-linear behavior of RMSD values for the evaluated temperatures. Thus, the results can be helpful to those who use this type of transducer attached to the printing bed for monitoring purposes.
Keywords: electret microphone; fused filament fabrication; monitoring; pencil lead breakage method; temperature influence